2018
DOI: 10.1007/s12170-018-0580-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment and Dietary Interventions in Older Patients with Heart Failure

Abstract: Purpose of Review Older patients with heart failure (HF) are challenging to manage due to the high prevalence of frailty, polypharmacy, cognitive impairment, and other geriatric conditions. Malnutrition and poor dietary habits are also common and strongly predict adverse outcomes in older patients with HF. Current dietary recommendations for HF primarily advise reducing sodium intake, but randomized studies suggest that excess restriction can lead to adverse outcomes. The optimal dietary pattern, caloric intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Based on these findings, it is essential to assess nutritional status and provide nutritional support in patients with HF, which might contribute to curbing the development of depressive symptoms. At present, consistent guidelines and recommendations for nutritional support are limited in patients with HF (Lee, Tam, Cascino, & Hummel, 2018). A previous review indicated that individualized nutritional interventions could be beneficial (Lee et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, it is essential to assess nutritional status and provide nutritional support in patients with HF, which might contribute to curbing the development of depressive symptoms. At present, consistent guidelines and recommendations for nutritional support are limited in patients with HF (Lee, Tam, Cascino, & Hummel, 2018). A previous review indicated that individualized nutritional interventions could be beneficial (Lee et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At present, consistent guidelines and recommendations for nutritional support are limited in patients with HF (Lee, Tam, Cascino, & Hummel, 2018). A previous review indicated that individualized nutritional interventions could be beneficial (Lee et al., 2018). A randomized controlled trial demonstrated that providing high‐quality diets according to the patients' nutritional needs, reducing barriers related to intake and providing nutritional supplements if needed, could significantly improve the prognosis of malnourished patients with HF (Bonilla‐Palomas et al., 2016).…”
Section: Discussionmentioning
confidence: 99%